Reviewer Acknowledgements - Williams, Richard (Journal of Agricultural Studies, 2021)
Journal of Agricultural Studies (JAS) would like to acknowledge the following reviewers for their assistance with peer review of manuscripts for this issue. Many authors, regardless of whether JAS publishes their work, appreciate the helpful feedback provided by the reviewers. Their comments and suggestions were of great help to the authors in improving the quality of their papers. Each of the reviewers listed below returned at least one review for this issue. Reviewers for Volume 9, Number 4 Ahmad Reza Pirali Zefrehei, Gorgan Univ. of Agricultural Sci. & Natural Resources, Iran Alessandra M. Lima Naoe, Federal University of Tocantins, Brazil André Luiz Rodrigues Magalhães, UFAPE, Brazil Camilla H. M. Camargos, University of Campinas, Brazil Emmanuel E. Omeje, University of Nigeria, Nigeria Eric Krawczyk, University of Michigan, USA Eric Owusu Danquah, CSIR-Crops Research Institute, Ghana Jorge A. López, University Tiradentes, Brazil Juliana Nneka Ikpe, Akanu Ibiam Federal Polytechnic, Nigeria Luh Suriati, Warmadewa University, Indonesia Nkemkanma Vivian Agi, Rivers State University Port Harcourt, Nigeria Raul Pașcalău, Banat’s University, Romania Saiful Irwan Zubairi, Universiti Kebangsaan Malaysia (UKM), Malaysia Shakirudeen Abimbola Lawal, University of Cape Town, South Africa Somaia Alkhair, Alzaeim Alazhari University, Sudan Toncho Gospodinov Penev, Trakia University, Bulgaria Zakaria Fouad Abdallah, National Research Centre, Egypt Richard Williams Editorial Assistant Journal of Agricultural Studies ————————————– Macrothink Institute 5348 Vegas Dr.#825 Las Vegas, Nevada 89108 United States Phone: 1-702-953-1852 ext.521 Email 1: jas@macrothink.org Email 2: jas@macrothink.com URL: http://jas.macrothink.org